A Developmental Study of Chinese EFL Learners’ Use of Discourse Markers in L2 Writing - Jing Lin (Journal of Linguistics and Communication Studies, 2023)
Discourse markers have pragmatic functions like promoting discourse fluency, expressing attitudes, constructing and managing coherence (Fraser, 1996; Halliday & Hasan, 1976). Most previous research focused on the use of specific discourse markers (Diskin, 2017; Gaines, 2011; Hasselgreen, 2004) or made a comparison between the non-native speakers and native speakers (Ament et al., 2018; Buysse, 2017; Liu, 2016; Wang & Wang, 2008) while the studies of the use of discourse markers from a developmental perspective are few. Therefore, this study aims to study discourse markers in L2 writings by describing and comparing the use of discourse markers used by the same group of Chinese EFL learners at varying proficiency levels. The participants in the current study are 30 English majors from the same grade. All of them are invited to write about the two same topics when they are sophomores and seniors. All of them have passed TEM-4 when they are sophomores. This study collects and analyzes data from their L2 writings. The researcher identifies and tags each discourse marker used in the L2 writings according to the function it has the context. After coding, the distribution, rate, and variety of discourse markers are calculated. The effect of varying language proficiency levels on the use of discourse markers is explored. Results indicate the continuation markers are used the most, followed by causal markers, contrast markers, sequencing markers, elaboration markers, opening and closing markers, summary or concluding markers, and topic shift or digression markers. The overall patterns of discourse markers’ distribution and rate in the two periods are similar while the total variety presents a difference that the seniors use more various discourse markers than the sophomores. The results suggest that language proficiency level is associated with discourse markers use. Participants of high proficiency use more various discourse markers. Therefore, the present study can contribute to our understanding of discourse markers through an in-depth analysis of L2 writing, improve EFL learners’ L2 writings quality and bring some important pedagogical implications for L2 writing assessment.